A Thirty-Minute Nap Enhances Performance in Running-Based Anaerobic Sprint Tests during and after Ramadan Observance - Yagin, Fatma Hilal; Eken, Özgür; Bayer, Ramazan; Salcman, Vaclav; Gabrys, Tomasz; Koç, Hürmüz; Yagin, Burak; Eken, İsmihan (International journal of environmental research and public health, 2022)
The purpose of this study was to determine the impact of a 30 min nap (N30) on the Running-Based Anaerobic Sprint Test (RAST) both during and after Ramadan. Ten physically active kickboxers (age: 21.20 ± 1.61 years, height: 174.80 ± 4.34 cm, body mass: 73.30 ± 7.10 kg and body mass index (BMI): 24.00 ± 2.21 kg/m2) voluntarily performed the RAST test after an N30 and in a no-nap condition (NN) during two experimental periods: the last ten days of Ramadan (DR) and ∼3 weeks after Ramadan (AR). During each DR-NN, DR-N30, AR-NN and AR-N30 protocol, kickboxers performed RAST performance. A statistically significant difference was found between Ramadan periods (DR vs. AR) in terms of max power (W) (F = 80.93; p1 < 0.001; η2p = 0.89), minimum power (W) (F = 49.05; p1 < 0.001; η2p = 0.84), average power (W) (F = 83.79; p1 < 0.001; η2p = 0.90) and fatigue index (%) results (F = 11.25; p1 = 0.008; η2p = 0.55). In addition, the nap factor was statistically significant in terms of the max power (W) (F = 81.89; p2 < 0.001; η2p = 0.90), minimum power (W) (F = 80.37; p2 < 0.001; η2p = 0.89), average power (W) (F = 108.41; p2 < 0.001; η2p = 0.92) and fatigue index (%) results (F = 16.14; p2 = 0.003; η2p = 0.64). Taking a daytime nap benefits subsequent performance in RAST. The benefits of napping were greater after an N30 opportunity for DR and AR.
Keywords: dospělí; lidé; Anaerobiosis; Fatigue; index tělesné hmotnosti; anaerobióza; spánek; Body Mass Index; Young Adult; Adult; mladý dospělý; Sleep; únava; Humans